DETERMINATION OF MEAN DYNAMIC TOPOGRAPHY IN INDONESIA USING ALTIMETRY SATELLITE - SYAHRULLAH FATHULHUDA (NIM : 25116005), MUHAMMAD
It has been widely understood that the Indonesian Geoid (vertical datum) is not yet officially available. In the meantime, one may use Mean Sea Level (MSL) values that are derived from 18 year of tide gauge observations. However, such MSL values may refer to different zero-palm height, and hence it seems impossible to have a seamless vertical datum from tide gauge observations. In addition, long records of tide gauge observations in Indonesia are not readily available. In this research, an alternative approach to have a seamless vertical datum is proposed. Here, a seamless MSL is derived through Mean Dynamic Topography (MDT) and geoid undulation. While accurate values of geoid undulation over the Indonesian region can be derived from EGM2008 model, the MDT has to be determined from long-term tidal observations as recorded by multi-mission Altimetry satellite. The purpose of this study is to identify the concepts and procedures for determining the MDT in Indonesia. The MDT is produced by subtracting the Mean Sea Surface (MSS), as derived from assimilation of Topex, Poseidon, Jason-1, GFO-1 and Envisat satellites, and geoid undulation model (EGM2008). In order to get accurate MSS, the altimetry data are corrected from any possible errors, and then they are co-lineared and filtered. The generated MDT is then compared with some global MDT models. The results indicate that the MDT generated in this study are in a good agreement with RMS deviation is approximately 2.27 cm (MDT-DTU10) and 7.48 cm (MDT-CNESCLS13), respectively. In addition, the level of proximity of the MDT model with MDT values from in-situ data is acceptable, when compared to MDT-DTU10 and MDT-CNESCLS13 models.